Contemporary Problems of Horrendous Evil - Rojka, Lubos (Nuovo Giornale di Filosofia della Religione (NGFR), 2021)
A study of the origins of modern atheism often leads to the religious and theological situation in the seventeenth century. Atheists found the arguments for their disbelief in various religious, theological, and philosophical theories which their defenders used against each other. A similar situation, which is not favorable to theism, exists nowadays in the debates regarding the problem of evil. The rationalistic, objective, or global approaches to the problem of evil in the analytical tradition are under attack from other schools and traditions, such as existential philosophy or apophatic as opposed to cataphatic theology.